Kedudukan Lembaga Bantu Dalam Sistem Kenegaraan Indonesia - Indithohiroh, Rosa; Yunus, Nur Rohim (Mavisha: Law and Society Journal, 2024)
Changes to the authority of the Financial Services Authority, namely Law Number 21 of 2011 concerning the Financial Services Authority by Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector resulted in the existence of a single authority which directly resulted in impunity for the authority of the main organ in investigating crimes in the financial services sector. The purpose of this research is to identify the essence of the position of auxiliary state institutions in Indonesian statehood. This research uses the statute approach and conceptual approach. The results of this study show that the implementation of auxiliary state institutions in Indonesia is still not by the essence of its formation as a supporting institution.   Perubahan atas kewenangan Otoritas Jasa Keungan pada Undang-Undang Nomor 21 Tahun 2011 tentang Otoritas Jasa Keuangan oleh Undang-Undang Nomor 4 Tahun 2023 tentang Pengembangan dan Penguatan Sektor Keuangan mengakibatkan terdapatnya penunggalan kewenangan yang secara langsung berakibat pada impunitas kewenangan main organ dalam penyidikan terhadap kejahatan di sektor jasa keuangan. Tujuan penelitian ini tentu untuk mengidentifikasikan esensi kedudukan lembaga negara bantu pada kenegaraan Indonesia. Penelitian ini menggunakan pendekatan perundang-undangan (statute approach) dan pendekatan konseptual (conceptual approach). Hasil dari penelitian ini menunjukan bahwa pengimplementasian mengenai lembaga negara bantu di Indonesia masih belum sesuia dengan esensi pembentukannya sebagai lembaga penunjang.